Molecular biosignatures reveal common benthic microbial sources of organic matter in ooids and grapestones from Pigeon Cay, The Bahamas. Issue 1 (4th July 2016) - O'Reilly, S. S.; Mariotti, G.; Winter, A. R.; Newman, S. A.; Matys, E. D.; McDermott, F.; Pruss, S. B.; Bosak, T.; Summons, R. E.; Klepac‐Ceraj, V.
Abstract: Ooids are sedimentary grains that are distributed widely in the geologic record. Their formation is still actively debated, which limits our understanding of the significance and meaning of these grains in Earth's history. Central questions include the role played by microbes in the formation of ooids and the sources of ubiquitous organic matter within ooid cortices. To address these issues, we investigated the microbial community composition and associated lipids in modern oolitic sands at Pigeon Cay on Cat Island, The Bahamas. Surface samples were taken along a transect from the shallow, turbulent surf zone to calmer, deeper water. Grains transitioned from shiny and abraded ooids in the surf zone, to biofilm‐coated ooids at about 3 m water depth. Further offshore, grapestones (cemented aggregates of ooids) dominated. Benthic diatoms and Proteobacteria dominated biofilms. Taxa that may promote carbonate precipitation were abundant, particularly those associated with sulfur cycling. Compared to the lipids associated with surface biofilms, relict lipids bound within carbonate exhibited remarkably similar profiles in all grain types. The enhanced abundance of methyl‐branched fatty acids and β‐hydroxy fatty acids, 1‐O‐monoalkyl glycerol ethers and hopanoids bound within ooid and grapestone carbonate confirms a clear association of benthic sedimentary bacteria with these grains. Lipids bound within ooid cortices also contain molecular indicators of microbial heterotrophic degradation of organic matter, possibly in locally reducing conditions. These included the loss of labile unsaturated fatty acids, enhanced long‐chain fatty acids/short‐chain fatty acids, enriched stable carbon isotopes ratios of fatty acids, and very high stanol/stenol ratios. To what extent some of these molecular signals are derived from later heterotrophic endolithic activity remains to be fully resolved. We speculate that some ooid carbonate forms in microbial biofilms and that early diagenetic degradation of biofilms may also play a role in early stage carbonate precipitation around ooids.